WOMEN’S LIBERTY IN RELIGIOUS DISCOURSE (NAWĀL AL-SA’DĀWĪ’S FANTASY IN ZĪNAH) - Yulia Nasrul Latifi (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
The objective of this research is to reveal Nawāl al-Sa’dāwī’s fantasy and to find out why she builds a fantasy of women’s autonomy in religious discourse as depicted in her latest novel, Zīnah. This study focuses on the concept of fantasy in Žižek's theory of subjectivity, which sees fantasy as a screen covering the lacks and inconsistencies of the shackling Symbolic. Fantasy is also an estuary of meaning that confirms the existence of a divided and dialectical subject that continues to move in search of self-fulfillment. The research method is hermeneutic, namely by interpreting the actions and fantasies of al-Sa’dāwī' as a subject. The analysis shows that al-Sa’dāwī’s fantasy is her realization of a transcendental humanist religious discourse which gives women full autonomy, internally and externally. Zīnah, the main character in the novel, is a symbol of this autonomy. Internally, Zīnah has been set free from the patriarchal shackles of religious discourses. Externally, Zīnah is able to change the structure and create a new humanist, transcendental, and progressive structure in religious discourse to liberate human beings. Zīnah is al-Sa’dāwī’s fantasy to cover up the lacks of The Symbolic, the estuary of meaning, and confirmation of her existence as a divided and dialectical subject. Tujuan penelitian ini adalah untuk mengungkapkan fantasi Nawāl al-Sa’dāwī dan mengapa Nawāl al-Sa’dāwī membangun fantasi otonomi perempuan dalam wacana agama yang tergambar dalam novel terakhirnya, Zīnah. Penelitian ini memfokuskan pada Fantasi yang ada dalam teori subjektivitas Žižek. Fantasi adalah layar yang menutupi kekurangan dan inkonsistensi dalam the symbolic yang membelenggu. Fantasi juga muara makna yang mengukuhkan eksistensi subjek yang terbelah dan berdialektik yang terus bergerak untuk mencari pemenuhan diri. Metode penelitian adalah hermeneutik dengan cara menafsirkan tindakan dan fantasi Nawāl al-Sa’dāwī sebagai subjek. Hasil analisisnya, fantasi Nawāl al-Sa’dāwī adalah terwujudnya wacana agama humanis transendental yang memberikan otonomi penuh perempuan, internal dan eksternal. Tokoh Zīnah adalah simbolisasi otonomi tersebut. Secara internal, Zīnah telah terbebas dari belenggu patriarki wacana agama. Secara eksternal, Zīnah mampu mengubah struktur dan membuat struktur baru yang humanis, transendental, dan progresif dalam wacana agama untuk membebaskan manusia. Zīnah adalah fantasi Nawāl al-Sa’dāwī untuk menutupi kekurangan the symbolic, muara makna, dan pengukuhan eksistensinya sebagai subjek yang terbelah dan berdialektika.